CONTRADICTION OVER THE APPLICATION OF CORPORATE LIABILITY IN CORRUPTION COURT DECISIONS IN INDONESIA - Suhariyanto, Budi; mustafa, cecep (UI Scholars Hub, 2023)
This paper presents and critically analyses the application of corporate criminal liability in the decisions of corruption crimes in Indonesia from 1999 to 2019. Of the seven corporate cases that have been prosecuted and convicted in this period. We identify 4 (four) corporate criminal liability models as follows. First, the corporation is accused, prosecuted, and convicted after the management has been convicted through a final and binding decision. Secondly, the corporation is excluded from the indictment but included in the sentencing. Third, the prosecution of corporate crimes negates the criminal liability of its management. Fourth, a portion of corporate criminal offenses is taken from the lack of punishment of its management. These four models cause a contradiction in normative perspectives. This paper contributes to the understanding of the context in which The Anti-Corruption Law shaped the judicial interpretation of corporate criminal liability